Indirect Versus Direct Bookings: Hotel Customer Motivations for Online Reservations at Travel Agencies in the Cape Metropole - Muresherwa, Gift; KYOMBA, MARLENE NGOIE; Spencer, John Peter (Acta Universitatis Danubius. Œconomica, 2022)
The emergency of several online travel agents (OTA) has come with several benefits for the potential travellers. Many accommodation establishments especially hotels find OTA helpful in this age of technological innovations and are using them as distribution channels for their products. This paper examines why hotel customers opt to book indirectly via OTA rather than making direct booking with the hotel. The paper also determines why hotel customers in Cape Metropole think it is cheaper and more convenient to make reservations through travel agents. Hotel customer behaviour when booking accommodation is also reviewed to establish the motivations in choosing a specific booking method. Three-hundred hotel guests participated in the study, and data analysed descriptively using the IBM Statistical Package for Social Sciences (SPSS). The study revealed a more inclination to OTA rather than direct reservation with the hotel, and this was mainly attributed to convenience and affordability. The study is of importance to hotels and OTAs as it advances understanding of booking behaviour of hotel customers. Recommendations on how hotels can attract and convince customers to book directly to help evade commissions to OTAs were discussed.